Rating rynków wschodzących Azji - Krawczyk, Patrycja (Ratings of emerging markets in Asia, 2009)
The term ‘emerging markets’ is used to describe a nation's social or business activity in the process of rapid growth and industrialization. Currently, there are around 25 emerging markets in the world, the Biggest Emerging Market (BEM) economies are Brazil, China, Egypt, India, Indonesia, Mexico, Poland, Philippines, Russia, South Africa, South Korea, and Turkey. A credit rating assesses the credit worthiness of an individual, corporation, or a country. These are assigned by credit rating agencies such as Standard & Poor's, Moody's or Fitch. The Standard & Poor's rating scale is as follows, from excellent to poor: AAA, AA, A, BBB, BB, B, CCC, CC, C, D. Anything lower than a BBB rating is considered a speculative or junk bond. The Moody's rating system is similar in concept but the naming is a little different. It is as follows, from excellent to poor: Aaa, Aa, A , Bbb, Bb, B, Ccc, Cc, C. Fitch Agency classifies China - A, India - BBB, Indonesia - BB, Korea - A , Malaysia - A, Philippines - BB, Taiwan - A, Thailand - BBB on a credit rating scale
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 307-314